Buddhism and the 21st century - Mungekar, Bhalchandra L. (Nava Nalanda Mahavihara, 2009)
section 1. Worldwide Buddhism : roots of the past -- section 2. International Buddhism : expressions around the world -- section 3. Engaged Buddhism : involvement in the present -- section 4. Social Buddhism : guide for the future